1990
DOI: 10.1161/01.str.21.11.1584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcranial and cervical continuous-wave Doppler in the evaluation of intracranial collateral circulation.

Abstract: Received May 23, 1989; accepted July 10, 1990. collaterals; compression of the common carotid artery is performed during insonation of the extracranial internal carotid artery and vertebral artery with a continuous-wave Doppler probe. Determination of communicating artery patency with this method correlated well with angiographic studies. 515 We compared the cerebral collateral patterns identified by both transcranial Doppler and continuous-wave Doppler (combined with compression maneuvers) and evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…There appeared to be no complications due to digital carotid compression in the present study, probably because healthy dogs were used. Similar results for its safety have been reported in human medicine (Padayachee and others 1986, Schneider and others 1988, Bass and others 1990). However, to avoid any associated problems, Bass and others (1990) recommended that compression should be of short duration to avoid ischaemic complications.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There appeared to be no complications due to digital carotid compression in the present study, probably because healthy dogs were used. Similar results for its safety have been reported in human medicine (Padayachee and others 1986, Schneider and others 1988, Bass and others 1990). However, to avoid any associated problems, Bass and others (1990) recommended that compression should be of short duration to avoid ischaemic complications.…”
Section: Discussionsupporting
confidence: 87%
“…Changes in the arterial flow following haemodynamic changes or cardiopulmonary resuscitation (Fukushima and others 2000), and following the administration of drugs such as sufentanil (Werner and others 1991), propofol (Werner and others 1992) or diuretics (Seo and others 2005) have been evaluated. Although previous studies did not describe the compression manoeuvres used in dogs, transcranial Doppler combined with common carotid artery compression is part of the routine procedure during transcranial Doppler ultrasonographic investigations to identify the brain‐supplying arteries in human patients, and has been shown to be an accurate and reproducible method for the evaluation of cerebral ischaemia and intracranial collateral circulation (Padayachee and others 1986, Schneider and others 1988, Bass and others 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Collateral flow pathways are of special significance when planning for carotid revascularization procedures [31], because their adequacy is the main determinant of cerebral blood flow in patients with severe carotid stenosis [32] and following cross-clamping. Several TCD studies have assessed intracranial collateral flow [ 10,22,26,[33][34][35]. We found that our original TCD criteria were 100% sensitive and 92% specific in identifying retrograde flow through the OA, and that the specificity could not be improved by increasing the OA peak systolic velocity to -30 em/sec.…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately, the patient numbers of the transcranial Doppler studies are too small to make a reliable comparison with our data. 19,30 Moreover, TCCD is considered a technique superior to conventional transcranial Doppler when exact measurements in small arterial segments are required. 16,31,32 It is of interest to compare our findings with the results of MR angiography, another new noninvasive technique for establishing the collateral integrity of the circle of Willis.…”
Section: Discussionmentioning
confidence: 99%